2020
DOI: 10.3390/electrochem1020012
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum-Suboxide Thin Films as Anode Layers in Planar Lithium Microbatteries

Abstract: In this paper, we investigate the effects of operational conditions on structural, electronic and electrochemical properties on molybdenum suboxides (MoO3-δ) thin films. The films are prepared using pulsed-laser deposition by varying the deposition temperature (Ts), laser fluence (Φ), the partial oxygen pressure (PO2) and annealing temperature (Ta). We find that three classes of samples are obtained with different degrees of stoichiometric deviation without post-treatment: (i) amorphous MoO3-δ (δ < 0.05) (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 156 publications
0
8
0
Order By: Relevance
“…1a). The octahedral It is a shallow donor and has a small formation energy in the O poor limit so that MoO3 easily becomes a degenerate semiconductor [71,72]. Figure 1d displays the XRD pattern of the layered α-MoO3 showing fingerprints at 2θ = 12.7°, 23.3°, 25.6°, 27.2°, and 38.9°, which correspond to the (020), ( 110), ( 040), (0.21) and (060) planes (JCPDS card no.…”
Section: Structurementioning
confidence: 99%
See 3 more Smart Citations
“…1a). The octahedral It is a shallow donor and has a small formation energy in the O poor limit so that MoO3 easily becomes a degenerate semiconductor [71,72]. Figure 1d displays the XRD pattern of the layered α-MoO3 showing fingerprints at 2θ = 12.7°, 23.3°, 25.6°, 27.2°, and 38.9°, which correspond to the (020), ( 110), ( 040), (0.21) and (060) planes (JCPDS card no.…”
Section: Structurementioning
confidence: 99%
“…Magnetic susceptibility measurements showed that MoO3, MoO2 and MonO3n-1 shear suboxides in between are all feebly paramagnetic. Copyright Lakshmi-Narayana et al [72]. Open access article under the CC BY-NC-ND license.…”
Section: Structurementioning
confidence: 99%
See 2 more Smart Citations
“…The commonly known crystalline phases for stochiometric molybdenum oxides are m-MoO 2 , α-MoO 3 , β-MoO 3 , MoO 3 , and h-MoO [36,[43][44][45]. This rich selection of molybdenum oxides has shown potential industrial applications such as sensors, cathodes for lithium ion batteries, photocatalyst, and supercapacitors, among others [45][46][47][48]. It is worth mentioning that both the MoO 2 and MoO 3 crystalline phases have been extensively studied and well characterized by Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%